Quality of life after first- and second- eye cataract surgery on community project in Lombok Island, West Nusa Tenggara, Indonesia (Faculty of Medicine Universitas Indonesia, 2013)
Background: This study aims to assess the quality of life and the time trade off-utility value of the first eye cataract surgery and the second eye cataract surgery in Lombok Island-Indonesia. Methods: This was an epidemiologic survey study on community of cataract surgery. Evaluations of quality of life (QoL) and time trade-off (TTO) were performed using questionnaire prior and three weeks after cataract surgeries who had either first (group A) or second eye cataract surgery (group B). Personal data was noted especially on self-care, mobility, socially, and mentally status. Data was analyzed by chi-square test for categorical data and unpaired t-test or Mann-Whitney test for numeric data. Results: A total of 77 subjects was included in this study, there were 50 subjects in group A and 27 subjects in group B. Elements of QoL were improved after surgeries including self care, mobility, social, and mental status in both groups (p < 0.001). The modified TTO was accepted in 35 subjects in group A and 22 subjects in group B. Quality of life was improved in 46 patients in group A, there was further improvement in 22 patients in group B. The degree of patient's expectation was good in 87% of all subjects. Conclusion: Second- eye cataract surgery showed further improvement in QoL despite better outcome of the first- eye cataract surgery. The outcome of cataract surgery conducted was relevant to the patientâs expectation. (Med J Indones. 2013;22:107-13)